Dynamic Response and Signal to Noise Ratio Investigation of NIR-FBG Dynamic Sensing System for Monitoring Thinwalled Composite Plate - Z. M., Hafizi; J. A., Epaarachchi (2015)
Optical fiber systems for dynamic response measurement become an attractive study nowadays especially in the field of Structural Health Monitoring (SHM). This work presents the investigation of an optical fiber sensor system utilizing Near Infra-Red Fiber Bragg Grating (NIR-FBG) sensor for SHM of a thin-walled composite structure. In this study, a comparison between the experimental result and simulation study using finite element analysis has been presented. By comparing both results, the FBG dynamic sensing system was shown to have an excellent capability in acquiring dynamic response due to flexural wave propagations. In the meantime, a signal to noise ratio (SNR) study was also performed to several FBG dynamic sensor systems; particularly to see the comparison between NIR-FBG sensor and 1550 nm FBG sensor. Furthermore, with a proper configuration, an NIR-FBG system was proved to have better performance than the 1550 nm based FBG sensor.